Kecemasan Orang Tua dan Imunisasi Dasar dimasa Pandemi Covid-19: Parents' Anxiety and Basic Immunization During the Covid-19 Pandemic - Fitriani Ningsih; Riska Ovany; Rizki Muji Lestari; Nomeri Yayan (Jurnal Surya Medika (JSM), 2023)
The COVID-19 pandemic situation has led to the temporary closure and/or delay of immunization services for community health centers in some areas. Parental anxiety about the risk of COVID-19 transmission is one of the factors in reducing immunization achievements, especially basic immunization. Parents' anxiety about the risk of COVID-19 transmission at this time is an obstacle that makes parents send their children for immunization. The purpose of this study was to determine the relationship between parental anxiety and completeness of basic immunization for infants during the Covid-19 pandemic at the Menteng Health Center. The design of this study used a cross sectional design. This research was conducted at the Menteng Health Center in July 2022. The population of this study were parents who had babies 0-12 months at the Menteng Health Center, Palangka Raya city and the sample size was 60 people using purposive sampling technique. . The test used in this study is the Chi-square test. The results showed that there was a relationship between maternal anxiety and immunization for infants during the COVID-19 pandemic (p value = 0.006 < 0.05). Therefore, for Puskesmas to improve health promotion regarding the importance of immunization, as well as socialize a series of health guidelines and protocols, such as the Guidelines for Immunization Services during the COVID-19 Pandemic for the provision of safe immunization services, safe immunization practices, and implementation of Standard Operating Procedures. Infection Prevention and Control in public health centres.